Tingkat Pengetahuan ASI Eksklusif pada Ibu Primipara di Dusun Pundong Kelurahan Srihardono Kecamatan Pundong Kabupaten Bantul - Endah Puji Astuti; Fara Adhiba (Journal of Health (JOH), 2017)
Background : Exclusive breastfeeding is the infant only breastmilk alone were given no food or liquid other than drugs, vitamins, and minerals. Primiparous mothers lack of knowledge about exclusive breastfeeding is good general, the definition of breastfeeding, benefit of breastfeeding, composition of breastfeeding, and how breastfeeding may be influenced by several factor, such as age, education, work, and resources, so that it can directly affect the success of exclusive breasfeeding.